2005
DOI: 10.1055/s-2005-870308
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Adult Long-term Survivors After Hemapoeitic Stem-cell Transplantation (HSCT)

Abstract: Thyroid function was evaluated in 72 adult survivors (41 females and 31 males) at 16 to 56 years of age, 1.5 years mean time (range 0.2 - 9.8) after hemapoeitic stem cell transplantation (HSCT) with no known prior history of thyroid dysfunction. Thyroid stimulating hormone (TSH) and free thyroxin levels (FT4) were determined before and after stimulation with thyrotropin releasing hormone (TRH). Conditioning regimens for HSCT did not include TBI. Overt hypothyroidism (basal TSH > 8 microIU/ml, FT4 < 0.8 ng/dl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
1
18
1
Order By: Relevance
“…1 The occurrence of thyroid dysfunction (TDF) as a complication of BMT and the factors associated with it have been described primarily in pediatric recipients of allogeneic BMT. [2][3][4] However, fewer studies have analyzed the incidence of this complication in adults, [5][6][7] in particular after autologous BMT. 5 In this study, we retrospectively analyzed the incidence of TDF in all consecutive adult BMT recipient survivors from our center for whom serial monitoring of thyroid-stimulating hormone (TSH) and free T4 (FT4) levels were available (n ¼ 169 adults; Table 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1 The occurrence of thyroid dysfunction (TDF) as a complication of BMT and the factors associated with it have been described primarily in pediatric recipients of allogeneic BMT. [2][3][4] However, fewer studies have analyzed the incidence of this complication in adults, [5][6][7] in particular after autologous BMT. 5 In this study, we retrospectively analyzed the incidence of TDF in all consecutive adult BMT recipient survivors from our center for whom serial monitoring of thyroid-stimulating hormone (TSH) and free T4 (FT4) levels were available (n ¼ 169 adults; Table 1).…”
mentioning
confidence: 99%
“…[2][3][4] However, fewer studies have analyzed the incidence of this complication in adults, [5][6][7] in particular after autologous BMT. 5 In this study, we retrospectively analyzed the incidence of TDF in all consecutive adult BMT recipient survivors from our center for whom serial monitoring of thyroid-stimulating hormone (TSH) and free T4 (FT4) levels were available (n ¼ 169 adults; Table 1). This population is representative of the overall BMT population for the same period (February 1993-April 2008) in terms of patient and transplant characteristics, such as type of BMT (autologous vs allogeneic), type of allogeneic donor (related vs unrelated), type of conditioning for allogeneic BMT (myeloablative vs non-myeloablative), gender, age at BMT, underlying disease and source of progenitors (data not shown).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Case studies have shown that a donor with autoimmune thyroid disorder may transfer cell capable of injuring the recipient's thyroid gland after hematopoietic stem cell transplantation (Lee et al 2001;Marazuela, and Steegman 2000). Immune-mediated thyroid injury arising in the host has been suggested in other studies and may be a form of graftversus-host-disease (Kami et al 2001;Katsanis et al 1990;Somali et al 2005). Patients receiving single-agent graft-versus-host-disease prophylaxis were found to have a 9.5 times greater risk of developing hypothyroidism than patients with multi-agent prophylaxis (Katsanis et al 1990).…”
Section: Allogeneic Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%